Assessment of microorganism activity as bio-preservatives for perishable food - Shevchenko Margarita; Zimina Maria; Sukhikh Stanislav; Gromov Yegor; Zubareva Elena (E3S Web of Conferences, 2021)
Analysis of the results of studying dynamics of microbiological indicators of perishable food (fresh tomatoes), shows that the control samples (fresh tomatoes without processing a preservative) on the 15th day of storage at 4±2 °C exceeds the QMA&OAMO index, on the 5th day yeast already detected. The activity of yeasts and molds on the surface of tomatoes treated with Nisin is reduced compared with the control. It was found that the new isolated microorganisms synthesizing bacteriocins exhibit the highest bioconservation efficiency compared to nisin and control. It was shown that QMA&OAMO does not exceed the maximum permissible value even at 35 days of storage, yeast and molds, E. coli group bacteria in 1.0 g and pathogenic microorganisms, including L. monocytogenes and Salmonella bacteria in 10.0 g were not detected in fresh tomatoes. As a result of the study of organoleptic quality indicators of perishable foods (fresh tomatoes), treated with selected strains of microorganisms (Bacillus subtilis, Lactobacillus rhamnosus, Pseudomonas putida and Psychrobacter immobilis), stored for 35 days at 4±2 °C revealed that fresh tomatoes on the 35th day keep fresh, the fruit is clean, excessive moisture of fruits is not observed. Also fresh tomatoes were characterized by an edible degree of maturity. The taste and smell of the tomatoes were consistent with the botanical variety, while no extraneous taste and smell were observed.